Cyberbullying among late adolescent: A cross-sectional study in two higher secondary schools of Kolkata, West Bengal - Saswati Mukherjee; Debasish Sinha; Abhishek De; Raghunath Misra; Amitabha Pal; Tushar Kanti Mondal (Wolters Kluwer Medknow Publications, 2019)
Cyberbullying is a newer phenomenon which is becoming more prevalent among adolescent students with the use of information technology. The objective of the study was to determine the prevalence of being cyberbullied among late adolescent and to study the behavior and the attitude on cyberbullying. It was a cross-sectional study conducted on 254 school students (15-19 years). Data were collected by self-administered questionnaire, and results were analyzed using SPSS version 20. About 210 (82.7%) students were using any form of social networking site and out of which 22 (10.5%) students were cyberbullied. Among those who were cyberbullied, the majority (16 [72.7%]) had no opinion and more than half (15 [68.2%]) sought their friends' help. Cyberbullying is emerging as a newer social problem in our country, where students' lack of awareness and understanding of it results in underreporting of cyberbullying incidents.